Challenges of big data adoption in Malaysia SMEs based on Lessig's modalities: A systematic review - Min Hooi Chuah; Ramayah Thurusamry (Cogent Business & Management, 2021)
This study aims to review the challenges of implementing big data analytics by Small and Medium Enterprises (SMES) in Malaysia. There is a lack of literature studies examining the relationship between Lessig's four modalities and the challenges of big data analytics adoption. This study assesses the implementation of Lessig's Four Modalities for the adoption of big data analytics in Malaysia SMEs based on literature review findings. To identify the challenges of applying big data analytics in Malaysian SMEs, a comprehensive literature search was conducted using databases, journals, Google Scholar, and IEEE publications. This research provides practical insights into the challenges of dealing with big data in SMEs. It is envisioned that Lessig's four modalities proposed in this study, namely legal, architecture, social, and market factors, can be applied by Malaysian SMEs to adopt big data analytics.
Keywords: 650; Big data analytics; challenges; Lessig’ s Four Modalities; legal; architecture; social; market; SMEs